The Effect of Knowledge of the Elderly and Family Caregivers on the Incidence of Readmission in the Elderly with Heart Failure: Systematic Review - Saraswati, Sarita; Rekawati, Etty; Sahar, Junaiti (STIKES Adi Husada, 2023)
Heart Failure (HF) is a progressive disease that occurs in 0.13% of Indonesia's population and is dominated by the elderly. This disease requires high costs due to high rehospitalization rates. In meeting their daily needs, the elderly with HF needs caregivers to pay attention to their health, prevent risk factors, and identify resources owned by the family to support the needs of the elderly with HF. The aim of this systematic review was to identify the effect of knowledge of elderly clients and caregivers on the incidence of re-hospitalization in the elderly with HF. The data collection method uses an electronic database from journals that have been published through ScienceDirect, EBSCOHost, ProQuest, ClinicalKey, and Scopus. The data was analyzed using PRISMA diagram. The results of the systematic review of related journals show that the knowledge of clients and caregivers can reduce the incidence of re-hospitalization, and worsening of conditions, and reduce the risk of mortality in heart failure patients, therefore good understanding and literacy is needed for caregivers and elderly clients with HF.